Genetic vulnerabilities upon inhibition of DNA damage response. Issue 14 (28th July 2021) - Wang, Chao; Tang, Mengfan; Chen, Zhen; Nie, Litong; Li, Siting; Xiong, Yun; Szymonowicz, Klaudia Anna; Park, Jeong-Min; Zhang, Huimin; Feng, Xu; Huang, Min; Su, Dan; et al.
Abstract: Because of essential roles of DNA damage response (DDR) in the maintenance of genomic integrity, cellular homeostasis, and tumor suppression, targeting DDR has become a promising therapeutic strategy for cancer treatment. However, the benefits of cancer therapy targeting DDR are limited mainly due to the lack of predictive biomarkers. To address this challenge, we performed CRISPR screens to search for genetic vulnerabilities that affect cells' response to DDR inhibition. By undertaking CRISPR screens with inhibitors targeting key DDR mediators, i.e. ATR, ATM, DNAPK and CHK1, we obtained a global and unbiased view of genetic interactions with DDR inhibition. Specifically, we identified YWHAE loss as a key determinant of sensitivity to CHK1 inhibition. We showed that KLHL15 loss protects cells from DNA damage induced by ATM inhibition. Moreover, we validated that APEX1 loss sensitizes cells to DNAPK inhibition. Additionally, we compared the synergistic effects of combining different DDR inhibitors and found that an ATM inhibitor plus a PARP inhibitor induced dramatic levels of cell death, probably through promoting apoptosis. Our results enhance the understanding of DDR pathways and will facilitate the use of DDR-targeting agents in cancer therapy.